The Cape Town Declaration on Vaccines 2012: Unlocking the full potential of vaccines in Africa. Issue 33 (19th July 2016) - Wiysonge, Charles S.; Waggie, Zainab; Hawkridge, Anthony; Schoub, Barry D.; Madhi, Shabir A.; Rees, Helen; Hussey, Gregory D.; ,
Abstract: Delegates at the first International African Vaccinology Conference noted, with dismay, that many African children have limited access to existing and new vaccines as a consequence of weak immunisation programmes, lack of political will, and high vaccine prices. This inequality is a denial of the African child her basic right to a healthy life, and jeopardises long term economic growth on the continent. In addition, there is insufficient emphasis in Africa on adolescent and adult immunisation. The delegates documented various concerns and made various commitments; contained in this Cape Town Declaration on Vaccines, adopted on 11 November 2012. Finally, delegates confirmed their agreement with the goals and strategic objectives of the Global Vaccine Action Plan, and committed to hold African leaders accountable for its implementation during the Decade of Vaccines. The full list of registered conference delegates is provided as supplementary data to this manuscript.